Disrupted interhemispheric coordination of sensory-motor networks and insula in major depressive disorder - Zhang, Chunguo; Jing, Huan; Yan, Haohao; Li, Xiaoling; Liang, Jiaquan; Zhang, Qinqin; Liang, Wenting; Ou, Yangpan; Peng, Can; Yu, Yang; Wu, Weibin; Xie, Guojun; et al. (Frontiers in Neuroscience, 2023)
Objective: Prior researches identified distinct neuroimaging characteristics between healthy controls (HCs) and patients with major depressive disorder (MDD). However, associations between homotopic connectivity and clinical characteristics in patients with MDD remain unclear. The present study aimed to explore the common and distinct homotopic connectivity patterns and their associations with clinical characteristics in patients with MDD. Methods: We recruited 42 patients with MDD and 42 HCs, and collected their clinical variables, potentially related indicators of eye movement, event-related potentials (ERPs) and resting-state functional magnetic resonance imaging (rs-fMRI) data. The data were analyzed using correlation analysis, support vector machine (SVM), and voxel-mirrored homotopic connectivity (VMHC). Results: Compared with HCs, patients with MDD had decreased VMHC values in the insula, and increased VMHC values in the cerebellum 8/vermis 8/vermis 9 and superior/middle occipital gyrus. SVM analysis which applied VMHC values in the cerebellum 8/vermis 8/vermis 9 and insula, or VMHC values in the superior/middle occipital gyrus and insula as inputs can distinguish HCs and patients with MDD with high accuracy, sensitivity, and specificity. Conclusion: The study demonstrated that decreased VMHC in the insula and increased VMHC values in the sensorimotor networks may be a distinctive neurobiological feature for patients with MDD, which might be served as potential imaging markers to discriminate HCs and patients with MDD.